Anxiety and Depression Are Not Related to Increasing Levels of Burden and Stress in Caregivers of Patients With Alzheimer's Disease. (12th February 2020) - Tentorio, Tiziana; Dentali, Sharon; Moioli, Camilla; Zuffi, Marta; Marzullo, Rosy; Castiglioni, Stefania; Franceschi, Massimo
Sixty-nine dyads of patients with Alzheimer's disease and primary caregivers have been followed up for 1 year to evaluate cognitive (Mini-Mental State Examination), functional (Instrumental Activities of Daily Living), and behavioral (Neuropsychiatric Inventory) decline of patient in relation to burden (Caregiver Burden Inventory), stress (Relative Stress Scale), anxiety (State-Trait Anxiety Inventory Y), and depression (Beck Depression Inventory) reported by the caregivers. After 1 year of observation, cognitive and functional scores worsened while behavioral problems remained unchanged and relatively mild in patients. After 1 year, caregivers' scores of scales of anxiety and depression decreased significantly, while stress scores remained unchanged and burden slightly increased. In our opinion, the unexpected improvement in psychological situation of caregivers may be mainly due to educational interventions focused on knowledge of the disease with a particular attention directed toward emotional support and individual needs.